La protección del derecho al debido proceso en el procedimiento administrativo de auditoría gubernamental realizado por la contraloría general del estado - Montesdeoca, Marcela V. (2020)
The present work studies "The Right Protection to Due Process in the Administrative Procedure from Government Audit carried out by the General Comptroller of the State", which has the general objective of How does due process guarantee in the administrative procedure executed by the General Comptroller of the State ?, for this, doctrine and legal laws have been checked as criteria by various jurists and treaty writers on concepts that were legally analyzed since the application of the Republic’s Constitution of Ecuador, International Agreements and Treaties, Organic Law of the General Comptroller of the State, the analysis of rulings that both the Constitutional Court of Ecuador and the National Court have issued regarding this issue, and the analysis if the General Comptroller of the State in its attributions and competences when determining the responsibilities of an administrative and civil nature, it does so according to the Due Process, mainly adhering to the principle of legality and impartiality or, on the contrary, this principle is violated by the control statements.